2006
DOI: 10.1590/s0100-41582006000100012
|View full text |Cite
|
Sign up to set email alerts
|

Efeito de fontes de silício na incidência e na severidade da antracnose do feijoeiro

Abstract: RESUMOForam realizados três experimentos para estudar a influência do silício na redução da antracnose, causada por Colletotrichum lindemuthianum, em feijoeiro (Phaseolum vulgaris). No primeiro experimento plantas tratadas com silicato de cálcio foram inoculadas com 0, 10 3 , 10 4 , 5x10 4 , 10 5 , 5x10 5 e 10 6 conídios/ml de C. lindemuthianum. Na concentração de 10 6 conídios/ml avaliou-se a diferença entre o silicato de cálcio e uma fonte de cálcio (óxido de cálcio). No segundo experimento foi avaliado o si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
21

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 9 publications
0
15
0
21
Order By: Relevance
“…Polanco et al (2012) reported that higher Si concentrations in the leaf tissues of bean plants supplied with this element were associated with a reduced area under the anthracnose progress curve in association with higher activities of chitinases, phenylalanine ammonia-lyases and lipoxygenases and an increased concentration of lignin. In the C. lindemuthianum-bean pathosystem, Si reduced both the area under the anthracnose incidence progress curve and the area under the anthracnose severity progress curve (Moraes et al, 2006). According to Menzies et al (1992), phenolics accumulated more rapidly in the epidermal cells of cucumber plants supplied with Si and colonized by Podosphaera xanthii.…”
Section: Introductionmentioning
confidence: 98%
“…Polanco et al (2012) reported that higher Si concentrations in the leaf tissues of bean plants supplied with this element were associated with a reduced area under the anthracnose progress curve in association with higher activities of chitinases, phenylalanine ammonia-lyases and lipoxygenases and an increased concentration of lignin. In the C. lindemuthianum-bean pathosystem, Si reduced both the area under the anthracnose incidence progress curve and the area under the anthracnose severity progress curve (Moraes et al, 2006). According to Menzies et al (1992), phenolics accumulated more rapidly in the epidermal cells of cucumber plants supplied with Si and colonized by Podosphaera xanthii.…”
Section: Introductionmentioning
confidence: 98%
“…The results of the present study, considered pioneering in the foliar application of Si to peach trees, suggest that sodium metasilicate has the potential to control M. fructicola, when applied at 14 to 7 days preharvest. The use of Si in the field to control diseases has been widely studied in recent years, for various species (Moraes et al 2006, Buck et al 2008, Duarte et al 2008, as well as its effect on inducing resistance, such as the formation of physical barriers, polyphenol synthesis (Chérif et al 1994, Gomes et al 2005, Hayasaka et al 2008) and fungal inhibition , Yang et al 2010. Spore germination was totally inhibited with the use of 6 g L -1 of sodium metasilicate ( Figure 2A) With respect to the assessment of fruit quality, no effect of sodium metasilicate application was observed on soluble solids and titratable acidity ( Figures 4A and 4B).…”
Section: Resultsmentioning
confidence: 99%
“…As informações obtidas foram integradas em curvas de progresso da doença e em áreas abaixo da curva de progresso da doença (AACPD) em cada tratamento (MORAES et al, 2006).…”
Section: Methodsunclassified